Genistein: A focus on several neurodegenerative diseases. Issue 7 (22nd April 2022) - Li, Rongzi; Robinson, Megan; Ding, Xiaowen; Geetha, Thangiah; Al‐Nakkash, Layla; Broderick, Tom L.; Babu, Jeganathan Ramesh
Abstract: Neurodegenerative diseases are caused by the progressive loss of function or structure of nerve cells in the central nervous system. The most common neurodegenerative diseases include Alzheimer's disease, Huntington's disease, motor neuron disease, and Parkinson's disease. Although the physical or mental symptoms of neurodegenerative disease may be relieved by various treatment combinations, there are currently no strategies to directly slow or prevent neurodegeneration. Given the demographic evidence of a rapidly growing aging population and the associated prevalence of these common neurodegenerative diseases, it is paramount to develop safe and effective ways to protect against neurodegenerative diseases. Most neurodegenerative diseases share some common etiologies such as oxidative stress, neuroinflammation, and mitochondrial dysfunction. Genistein is an isoflavone found in soy products that have been shown to exhibit antioxidant, anti‐inflammation, and estrogenic properties. Increasing evidence indicates the protective potential of genistein in neurodegenerative disorders. In this review, we aim to provide an overview of the role that genistein plays in delaying the development of neurodegenerative disease. Practical applications: Genistein is a naturally occurring isoflavone found mainly in soybean, but also green peas, legumes, and peanuts. Genistein is found to pass through the blood–brain barrier and possess a neuroprotective effect. In this review, we discuss studies in support of these actions and the underlying biological mechanisms. Together, these data indicate that genistein may hold neuroprotective effects in either delaying the onset or relieving the symptoms of neurodegenerative disease. Abstract : The effect of genistein on neurodegenerative disease.